Perforator flaps for vulvar reconstruction: basic principles - Raposio, Edoardo; Moioli, Melita; Raposio, Giorgio; Spinaci, Stefano; Cagnacci, Angelo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: In vulvar cancer, the standard treatment is radical local excision, with immediate reconstruction. Reconstruction aims to restore anatomy and function of the external female genitalia, facilitating preservation of normal body image, sexual function, and micturition and defecation functions. Methods: The purpose of this paper is to describe the principles of perforator flaps for vulvar reconstruction. Results: Basic concepts, indications and operative technique are discussed and detailed. Conclusions: In vulvar reconstruction, the use of perforator flaps is a superior surgical technique when compared to the use of conventional flaps.